2023
DOI: 10.17113/ftb.61.02.23.7929
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Folate Biosynthesis Genes in Lactic Acid Bacteria from Different Sources

Abstract: Research background. Lactic acid bacteria (LAB) are known to produce folate. However, this ability is highly strain-dependent. Folate synthesis in specific LAB strains is affected by the availability of folate, which can be consumed by LAB under certain conditions. Moreover, differences in folate synthesis capabilities are related to the presence of folate biosynthesis-related genes and regulation of this pathway. Experimental approach. As basic information to better understand the regulation of folate biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Mahara et al tested 13 LAB and found that 11 had eight genes involved in folate biosynthesis (folE, folQ, folB, folK, folP, folC1, folA and folC2) and these isolates had the ability to produce folate. 48 However, the other two isolates that do not produce folate lack genes such as folQ, folP and folA. These results indicated that utilizing genome analysis and KEGG annotation is a fast and effective way to explore the potential folate synthesis ability of microorganisms.…”
Section: Pathways Related To Folate Synthesismentioning
confidence: 95%
“…Mahara et al tested 13 LAB and found that 11 had eight genes involved in folate biosynthesis (folE, folQ, folB, folK, folP, folC1, folA and folC2) and these isolates had the ability to produce folate. 48 However, the other two isolates that do not produce folate lack genes such as folQ, folP and folA. These results indicated that utilizing genome analysis and KEGG annotation is a fast and effective way to explore the potential folate synthesis ability of microorganisms.…”
Section: Pathways Related To Folate Synthesismentioning
confidence: 95%
“…Therefore, it has been suggested that folate-producing LAB are unable to reduce oxidized pterin compounds and do not possess a pterin salvage pathway ( de Crécy-Lagard et al, 2007 ; Noiriel et al, 2007 ). Moreover, LAB possessing incomplete genes in the DHPPP (pterin compounds) biosynthetic pathway are unable to synthesize folate ( Mahara et al, 2023 ). This indicates that these LAB cannot produce folate because they cannot produce or salvage pterins.…”
Section: Folate Salvage Pathwaymentioning
confidence: 99%